Ti3C2Tx-UHMWPE nanocomposites—Towards an enhanced wear-resistance of biomedical implants - Rothammer, Benedict; Feile, Klara; Werner, Siegfried; Frank, Rainer; Bartz, Marcel; Wartzack, Sandro; Schubert, Dirk W.; Drummer, Dietmar; Detsch, Rainer; Wang, Bo; Rosenkranz, Andreas; Marian, Max (Journal of Biomedical Materials Research Part A, 2024)
There is an urgent need to enhance the mechanical and biotribological performance of polymeric materials utilized in biomedical devices such as load-bearing artificial joints, notably ultrahigh molecular weight polyethylene (UHMWPE). While two-dimensional (2D) materials like graphene, graphene oxide (GO), reduced GO, or hexagonal boron nitride (h-BN) have shown promise as reinforcement phases in polymer matrix composites (PMCs), the potential of MXenes, known for their chemical inertness, mechanical robustness, and wear-resistance, remains largely unexplored in biotribology. This study aims to address this gap by fabricating Ti3C2Tx-UHMWPE nanocomposites using compression molding. Primary objectives include enhancements in mechanical properties, biocompatibility, and biotribological performance, particularly in terms of friction and wear resistance in cobalt chromium alloy pin-on-UHMWPE disk experiments lubricated by artificial synovial fluid. Thereby, no substantial changes in the indentation hardness or the elastic modulus are observed, while the analysis of the resulting wettability and surface tension as well as indirect and direct in vitro evaluation do not point towards cytotoxicity. Most importantly, Ti3C2Tx-reinforced PMCs substantially reduce friction and wear by up to 19 and 44 %, respectively, which was attributed to the formation of an easy-to-shear transfer fil
Keywords: 2D materials; MXenes; UHMWPE; polymer matrix composites; biotribology